Préjudice Matériel, Corporel Et Moral: Variations Sur La Classification Tripartite Du Préjudice Dans Le Nouveau Droit De La Responsabilité - Vézina, Nathalie (Revue de droit de l'Université de Sherbrooke, 1993)
Traditionally, when a victim sought damages, the injury would be categorized as material or moral, depending on whether a patrimonial interest was involved. Under the new Civil Code of Quebec, key articles relating to civil liability divide injuries into three separate categories. In so doing, the Quebec Legislator confirms a jurisprudential and doctrinal trend which considers bodily injury as distinct from the two categories mentioned above. The writer notes that this classification will have a greater impact on the rules concerning civil liability than that which existed under the Civil Code of Lower Canada, since several articles apply differently depending on the nature of the injury suffered by the victim. In addition, she examines some of the difficulties that may arise in the application of this newly recognized classification.